BINDER EFFECTIVENESS ON COTTON FABRIC FINISHING WITH MICROCAPSULES USING PADDING - agus surya mulyawan; tatang wahyudi (Arena Tekstil, 2018)
One of the processes to improve the function of cotton fabric is microcapsule finishing. Microcapsules are expected to have adequate resistance to surface of cotton fabric. However, since microcapsule shell has no chemical bond with cotton fabric, a binder is used for example polyacrylic and polyurethane. The aim of this research is to study the effectiveness of polyacrylic and polyurethane binder in cotton fabric microcapsule finishing using padding technique. The cotton fabric is immersed in a solution of microcapsules and binder for (5-10) minutes at room temperature, press with 90% Wet Pick Up (WPU), dried at 100 ° C for 60 seconds then followed by a temperature of 110 ° C for 120 seconds. The cotton finishing fabric of microcapsule observed from its surface with Scanning Electron Microscope (SEM), tested its washing fastness with Launder-O-meter, its tensile strength with tensile tester, and its stiffeness with stiffeness tester. Particle size of microcapsules analyzed with Particle Size Analyzer (PSA), and shell of microcapsule with Fourier Transform Infra Red (FTIR). Results showed that the microcapsule size of 1.14 μm with melamine formaldehyde shell, the use of polyacrylate and polyurethane binder could maintain the microcapsules in the fabric up to ten times, increase the tensile strength and stiffness of cotton fabric.